Natural products : a laboratory guide - Ikan, Raphael, 1927-2013 (Academic Press, 1991)
This new edition has been updated to include the following: The use of biomarkers (organic compounds in the geospherical record with carbon skeletons) reflecting the upsurge in geoporphyrin research primarily due to MS, yeast RNA nucleic acid studies: reversed-phase HPLC of amino acids; brewing industry applications (HPLC evaluation of carotenoids in orange juice and of "debittered" citrus); HPTLC of carbohydrates; synthesis of a sweetening agent from citrus peels, synthesis and degradation of alkaloids and of sterols, GC/MS uses with sterols, petroleum products, and aromatic constituents of wine and grape juice, flash chromatography of essential oils, optical purity of enantiomers affecting flavors, fragrances, and pheromones, as well as studies of lattice inclusion compounds 1H- and 13C-NMR, MS, IR and UV data are presented for most natural products